2D.05: RELATIONSHIP OF CORONARY ATHEROSCLEROSIS WITH ARTERIAL STIFFNESS AND CENTRAL SYSTOLIC BLOOD PRESSURE. (June 2015) - Tarnoki, A.; Tarnoki, D.L.; Godor, E.; Littvay, L.; Horvath, T.; Jermendy, A.; Merkely, B.; Jermendy, G.; Maurovich-Horvat, P.
Abstract : Objective: Arterial stiffness, an independent predictor of cardiovascular disease has been associated with the presence and extent of coronary artery calcification (CAC). We sought to assess the relationship between various hemodynamic parameters and presence of coronary atherosclerotic plaques. Design and method: In a prospective study 213 subjects (76 men and 137 women, mean age 56 ± 9 years) underwent oscillometry (TensioMed Arteriograph, Medexpert Ltd., Budapest, Hungary), CAC scoring and coronary CT angiography (CTA) (256-slice Brilliance iCT, Philips Healthcare, Best, The Netherlands). The association of aortic pulse wave velocity (PWV), brachial and central systolic blood pressure (SBP) with the presence of calcified and non-calcified plaques was analyzed with multivariate logistic regression (SPSS Statistics 17). Results: Those presenting with CAC were on average 10 years older (n = 47). Subjects with > 0 total CAC score in comparison to subjects with no CAC had a significantly higher brachial (128 ± 16.3 vs. 122 ± 14 mmHg) and central systolic blood pressure (SBP, 129 ± 22 vs. 121 ± 17 mmHg) and aortic pulse wave velocity (10 ± 2 vs. 8 ± 2 m/s), all p < 0.01. Subjects with any calcified or non-calcified plaques on coronary CTA had a higher brachial SBP, aortic PWV (both p < 0.01) and SBP (p < 0.05). Controlling for sex, age and age-squared in a regression, >0 total CACS (B = 0.983, p < 0.01), any atherosclerotic plaque (B = 1.286, p < 0.001) were both significantly associated with higher aortic PWV, but not with brachial or central systolic blood pressure. Conclusions: Patients with coronary atherosclerosis have a higher arterial stiffness. However, we did not find a association between arterial stiffness and systolic or central blood pressure. Further studies are warranted to evaluate the predictive value of arterial stiffness in coronary atherosclerotic risk assessment.